Role of Zooplankton in Aquatic and Sea Environments (Journal of Advances and Scholarly Researches in Allied Education, 2024)
An aquatic ecosystem is one that is mostly or entirely supported by water, whether it be in the form of a lake, river, pond, or ocean. changes and stresses in the environment might affect stock recruitment.  Integrating recruitment models with biological indicators might be beneficial for future stock levels.  The number of predators like fish may be inferred from zooplankton populations, which in turn reflect the state of the ecosystem and the living component.  Because of their essential role in the food web, zooplankton species can influence fish populations and the processes that bring new fish into the water.  A domino effect that affects fish populations may be set in motion by changes in zooplankton biomass abundance. The biotic component consists of living organisms in the water (such as fish, planktons, annelids, etc.) and how they interact with their environment. Zooplankton have an effect on how ecosystems function. Zooplankton play a dual role in the food web, both as grazers of algae and bacteria and as providers of nitrogen and phosphorus to phytoplankton . A perfect nutrient recycling cycle is achieved.